Equatorial Guinea and northern Gabon margins : regional tectonic evolution based on integrated analysis of seismic reflections and potential field data and modeling - Williams, Ehimen (2008)
The quest to unravel and better constrain the crustal architecture and related geological processes of South Atlantic margins underscores the importance of this study. This is true considering the huge economic prospect derivable from this region, especially in the petroliferous conjugate margins of West Africa and Brazil (Cameron et al., 1999). The opening of the South Atlantic Ocean is attributed to the Mesozoic breakup of Gondwana super-continent. The breakup led to the splitting of Proterozoic cratonic blocks (e.g. Sao Francisco and Congo cratons) amalgamated during the Late Precambrian when the Brazilian and Pan African orogenies took place in the west and east parts of the cratonic nucleus, respectively (Alkmin, 2004). The evolution of varied basinal architectures within the South Atlantic conjugate margins took place in response to complex extensional and magmatic regimes initiated during the breakup process. There is a strong rheological control on the overlying Mesozoic-Cenozoic sedimentary basins along the conjugate margins, induced by the underlying different basement terranes which influence the structural evolution of the syn–rift sections (Rosendahl et al., 2005) There have been ambiguities regarding the exact position of the continent-ocean boundary during plate motion reconstructions and early stages of seafloor spreading in the South Atlantic margins. Firstly, the presence of a magnetic quiet zone from early Aptian to Campanian times is inferred as a major obstacle limiting research into anomalies arising from seafloor spreading at neighboring continental margins (Chang et al., 1992). Secondly, the presence of halokinetic structures (e.g. salt diapirs) along the South Atlantic margins blurs the efficient imaging and effective analysis of the syn-rift features (Katz et al., 2000). The bathymetric features in the South Atlantic are fairly symmetric with the central axis being the mid-ocean ridge. This ridge is confined by several structures on both sides of the abyssal plain, the most prominent ...